PEMBUKTIAN TERBALIK DALAM PEMERIKSAAN TINDAK PIDANA KORUPSI DI INDONESIA - SH, Nurhayani (Jurnal IUS, 2015)
The number of cases of corruption have led to public distrust of the legal and criminal justice system. One of the verification system in case of corruption is reversed burden of proof. This study aimed to analyze the reversed burden of proof in terms of what is charged to the defendant in a corruption case, analyzing the application of reversed burden of proof in cases of corruption and constraints. This thesis research type is research of normative law. The theory used is the theory of law enforcement, evidence theory, the theory of justice. Results of the research that has been done is reversed burden of proof in cases of corruption applied to bribery accept gratuities worth 10 million upwards and towards proving property belonging to the defendant who has not been charged but allegedly derived from criminal acts of corruption as well as the adoption of reverse authentication is done by the judge ordered the defendant to prove that his property obtained legally. Barriers to implementation of proof in terms of the substance of the law is still weak because it is still limited to the recognition of rights of the accused but not the obligation defendant to prove the upside, in terms of legal culture is still dominant prosecution to prove the charges.Keywords: Evidence upside, Inspection, corruption